Perceptions of Higher Education Service Quality Have a Significant Influence on Predictors of Student Subjective Well-Being - Putri, Asri Mutiara; Lutfianawati, Dewi (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
Subjective well-being is an important mental health indicator to study in students because it significantly predicts academic achievement and college dropout rates. This research aims to determine the influence of perceptions of the quality of higher education services, social support, and self-regulation on students' subjective well-being. The sample in this study was 325 students from various universities in Indonesia. The data in this research was obtained through the Student Subjective Well-Being questionnaire, the Higher Education Performance scale, the Multidimensional Scale of Perceived Social Support, and the Self-Regulation Questionnaire to measure the variables in this research. The collected data was then analyzed using linear multiple regression. The results of this study indicate that students' perceptions of the quality of higher education services, social support, and self-regulation significantly affect students' subjective well-being. Student perceptions of the quality of higher education services were established as the main predictor of students' subjective well-being. The results of this research imply that to improve students' subjective well-being, an approach is needed that includes quality services from the university, social support, and good self-regulation skills for students.